Question
upstudy study bank question image url

a) Encuentren dos soluciones para \( x \) en cada ecuación. \( \begin{array}{ll}x^{2}+4 x=0 & x=\square y x= \\ 2 x^{2}-8 x=0 & x= \\ 3 x^{2}+15 x=0 & y x= \\ 4 x^{2}-6 x=0 & x= \\ x^{2}+9 x=0 & y x=\end{array} \)

Ask by Simmons Mills. in Mexico
Feb 24,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

Las soluciones para cada ecuación son: 1. x² + 4x = 0 → x = 0 y x = –4 2. 2x² – 8x = 0 → x = 0 y x = 4 3. 3x² + 15x = 0 → x = 0 y x = –5 4. 4x² – 6x = 0 → x = 0 y x = 3/2 5. x² + 9x = 0 → x = 0 y x = –9

Solution

Vamos a resolver cada una de las ecuaciones factorizando. 1) Para x² + 4x = 0:  Factorizamos: x(x + 4) = 0.  Entonces, x = 0 o x + 4 = 0 → x = –4.  Soluciones: x = 0 y x = –4. 2) Para 2x² – 8x = 0:  Factorizamos: 2x(x – 4) = 0.  Entonces, 2x = 0 → x = 0 o x – 4 = 0 → x = 4.  Soluciones: x = 0 y x = 4. 3) Para 3x² + 15x = 0:  Factorizamos: 3x(x + 5) = 0.  Entonces, 3x = 0 → x = 0 o x + 5 = 0 → x = –5.  Soluciones: x = 0 y x = –5. 4) Para 4x² – 6x = 0:  Factorizamos: 2x(2x – 3) = 0.  Entonces, 2x = 0 → x = 0 o 2x – 3 = 0 → x = 3/2.  Soluciones: x = 0 y x = 3/2. 5) Para x² + 9x = 0:  Factorizamos: x(x + 9) = 0.  Entonces, x = 0 o x + 9 = 0 → x = –9.  Soluciones: x = 0 y x = –9.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

Para la primera ecuación \( x^{2}+4x=0 \), podemos factorizar: \( x(x+4)=0 \). Esto nos da las soluciones \( x=0 \) y \( x=-4 \). En la segunda ecuación \( 2x^{2}-8x=0 \), factorizamos comode \( 2x(x-4)=0 \), resultando en \( x=0 \) y \( x=4 \). Continuando con \( 3x^{2}+15x=0 \), factorizamos como \( 3x(x+5)=0 \), dando \( x=0 \) y \( x=-5 \). Para \( 4x^{2}-6x=0 \), factorizamos: \( 2x(2x-3)=0 \), así que tenemos \( x=0 \) y \( x=\frac{3}{2} \). Finalmente, en la última ecuación \( x^{2}+9x=0 \), factorizamos a \( x(x+9)=0 \), resultando en \( x=0 \) y \( x=-9 \). Así que las soluciones son: - \( x^{2}+4x=0: x=0, x=-4 \) - \( 2x^{2}-8x=0: x=0, x=4 \) - \( 3x^{2}+15x=0: x=0, x=-5 \) - \( 4x^{2}-6x=0: x=0, x=\frac{3}{2} \) - \( x^{2}+9x=0: x=0, x=-9 \)

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy